Análise dos atendimentos do SAMU 192: componente móvel da Rede de Atenção às Urgências e Emergências - Almeida, Priscila Masquetto Vieira de [UNESP] (2014)
The fast and unplanned growth of cities has led important epidemiological changes, especially when referring to the growth of diseases related to emergency situations. The Ministry of Health proposes action as the condition for deployment of Network for Health Care, highlighted the Network for Emergency Care. Currently SAMU - 192 is the main component of the mobile for the Network for Emergency Care, to decrease the number of deaths, the sequela caused by delays in care and hospital stay. In Botucatu the service began in 2011, is a regional character and, besides ambulances , has a Central Regulatory Urgency and Emergency . This study aimed to analyze the services performed by SAMU-192: mobile component of the Network Emergency Care and Emergencies, in Botucatu-SP. This is an exploratory - descriptive field study of time series, a quantitative approach. The study focused on the analysis of the care provided by SAMU - 192, Botucatu between August 2011 and January 2012 , based on 2635 Attendance Sheets . The study had a favorable opinion of the institution's Ethics Committee and Research (Of. 3907/2012). The results showed that the majority of victims were male (53 %), adults demanded larger numbers of attendances. The primary nature of the clinical occurrence was attended, agreeing with other studies. The Basic Support Unit was responsible for the majority of treatment (66.57 %), the Advanced Support Unit was associated with the occurrence of psychiatric care (p = 0.0002). The main clinical complaints were met seizure (12.16%) , which was associated with the adult population (p < 0.0001), drunkenness (9.95 %) which was associated with male gender (p < 0.0001) and adults (p < 0.0001), and chest pain (8.15%) that was associated with the adult population. Traumatic complaints that stood out were nonspecific fall (23.05%) that joined the adult population, and fall from height (22.34%) which was associated with the elderly population. As for ...